SISTEM ANTRIAN REKAM MEDIS PASIEN DI RUMAH SAKIT MENGGUNAKAN MODEL MULTI CHANNEL DENGAN POLA POISSON - Yeyi Gusla Nengsih (Akademi Perekam dan Informasi Kesehatan Imelda, 2020)
Queue is an occurrence where someone has to wait their turn to get service. Queuing processes in hospitals when processing outpatient registration medical records at the hospital often occur especially during peak hours. To overcome this problem, a solution is needed to improve service performance at the hospital. The queuing model used is the Multi Channel-single phase queuing model which has one or more services flowing by a single queue. The variables to be observed are time between arrivals, service time data and number of services assuming a Poisson distribution pattern. The results of this study will show the operator's busy time is 83.33%, the number of queues in a certain period (Lq) is 13 patients, the number of registrants in the system (L) is 14 patients, the waiting time in the queue (Wq) is 24 minutes, and waiting time in the system (W) is 30.06 minutes.